Efektivitas Latihan Aerobik Dalam Mengurangi Gejala Depresi: Literature Review - Giriyoga, Putra Adytio; Alpiah, Dini Nur (UI Scholars Hub, 2025)
Depression is one of the most common mental health disorders worldwide and can significantly affect an individual's quality of life. Various treatment approaches have been implemented, with one of the most noteworthy being non-pharmacological interventions in the form of aerobic exercise. This study aims to review the effectiveness of aerobic exercise in reducing depressive symptoms. This research is a narrative literature review, in which 3,610 articles were initially identified and then filtered based on inclusion-exclusion criteria, resulting in 8 articles. After eliminating duplicates, further screening was conducted through critical appraisal. The final selection of 8 articles was reviewed. The findings from the review indicate that aerobic exercise is proven to improve mood, reduce depression scores, and enhance patients' quality of life.